Five thousand years of fire history in the high North Atlantic region: Natural variability and ancient human forcing - Segato D.; Villoslada Hidalgo M. D. C.; Edwards R.; Barbaro E.; Vallelonga P.; Kjaer H. A.; Simonsen M.; Vinther B.; Maffezzoli N.; Zangrando R.; Turetta C.; Battistel D.; et al. (Climate of the Past, 2021)
Biomass burning influences global atmospheric chemistry by releasing greenhouse gases and climate-forcing aerosols. There is controversy about the magnitude and timing of Holocene changes in biomass burning emissions from millennial to centennial timescales and, in particular, about the possible impact of ancient civilizations. Here we present a 5gkyr record of fire activity proxies levoglucosan, black carbon, and ammonium measured in the RECAP (Renland ice cap) ice core, drilled in coastal eastern Greenland, and therefore affected by processes occurring in the high North Atlantic region. Levoglucosan and ammonium fluxes are high from 5 to 4.5gkyrgBP (thousand years before 2000gCE) followed by an abrupt decline, possibly due to monotonic decline in Northern Hemisphere summer insolation. Levoglucosan and black carbon show an abrupt decline at 1.1gkyrgBP, suggesting a decline in the wildfire regime in Iceland due to the extensive land clearing caused by Viking colonizers. All fire proxies reach a minimum during the second half of the last century, after which levoglucosan and ammonium fluxes increase again, in particular over the last 200 years. We find that the fire regime reconstructed from RECAP fluxes seems mainly related to climatic changes; however over the last millennium human activities might have influenced wildfire frequency/occurrence substantially.